AS FONTES NO PODCAST MAMILOS: UMA PROPOSTA DE ANÁLISE AUDIOESTRUTURAL - SILVA, Gessiela Nascimento da (2022)
The sources are essential to the construction of the identity of a podcast and its relationship with the audience. Thus, this research investigates the organization of Mamilos: Open Chest Dialogues, through the sources used throughout the episodes. Situated in the podosphere since 2014, the weekly program fits into the structure of debate and presents itself as a space to dialogue about the issues that gain notoriety in networks and social media, along with guests. To get to the central element of the research, we trace a path from radio to webradio, with contributions from Ferraretto (2014); Kischinhevsky, Lopez and Zuculoto (2020) to understand the relationship of the medium with the podcast and punctuate the emergence in the national and global sphere and the changes that have occurred, signaled by Assis (2012), Luiz (2011; 2014) and Viana (2018; 2019; 2020). In the sequence, the behavior and the academic production on the theme in national events of the area and in Post-Graduation Programs in Communication and Journalism were observed. When discussing sources in the podcast, we found intersections between the field of journalism, radio and internet (SCHMITZ, 2011; LOPEZ, 2009; 2010, RUTILLI, 2014, CHAGAS 2020; 2018), but with gaps in the podosphere: which signals a question for future analysis. Within this scope, 86 episodes were projected for collection between 2014 to 2021, based on the artificial month technique (HERSCOVITZ, 2010) in which each day or week can be from a specific month. However, only 80 episodes were validated, as two issues were noted: i) no publication in the selected week; ii) vacation of the presenters. In order to meet the research objectives, the Podcast Audiostructural Analysis was applied, a methodological proposal to understand the organization of sources in Mamilos, and from them, look at other elements: profile of the program and the content covered. As a result, it is observed that the program organizes the contents based on the social events most discussed in social networks; the sources used are mostly experts, followed by notables, which denotes a concern with the listener in transmitting and creating dialogues between people with technical knowledge about the specific field. This would be a way to maintain trust and credibility, values strengthen the relationship with partners and sponsoring brands of the podcast.